Using viruses as nanomedicines - van Kan-Davelaar, H E (Br J Pharmacol, 2014)
The field of nanomedicine involves the design and fabrication of novel nanocarriers for the intracellular delivery of therapeutic cargo or for use in molecular diagnostics. Although traditionally recognized for their ability to invade and infect host cells, viruses and bacteriophages have been engineered over the past decade as highly promising molecular platforms for the targeted delivery and treatment of many human diseases. Inherently biodegradable, the outer capsids of viruses are composed entirely of protein building blocks, which can be genetically or chemically engineered with molecular imaging reagents, targeting ligands and therapeutic molecules. While there are several examples of viruses as in vitro molecular cargo carriers, their potential for applications in nanomedicine has only recently emerged. Here we highlight recent developments towards the design and engineering of viruses for the treatment of cancer, bacterial infections and immune system-related diseases. LINKED ARTICLES: This article is part of a themed section on Nanomedicine. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue-17